2014
DOI: 10.1038/nrn3827
|View full text |Cite
|
Sign up to set email alerts
|

Time cells in the hippocampus: a new dimension for mapping memories

Abstract: Recent studies have revealed the existence of hippocampal neurons that fire at successive moments in temporally structured experiences. Several studies have shown that such temporal coding is not attributable to external events, specific behaviours or spatial dimensions of an experience. Instead, these cells represent the flow of time in specific memories and have therefore been dubbed ‘time cells’. The firing properties of time cells parallel those of hippocampal place cells; time cells thus provide an additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
604
1
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(643 citation statements)
references
References 102 publications
30
604
1
8
Order By: Relevance
“…The vivid recall that participants engaged in during the current study might be considered to have favored the kind of first-person perspective remembering associated with egocentric processing. Moreover, whereas the hippocampus may integrate elements of an episodic memory such as space and time (Burgess et al, 2002;Eichenbaum, 2014), AnG may integrate sensory elements of multimodal memories into a complete and vivid recollection. Examining the possible functional dissociation between these two regions is a critical next step for future research.…”
Section: Angular Gyrus and Episodic Memorymentioning
confidence: 99%
“…The vivid recall that participants engaged in during the current study might be considered to have favored the kind of first-person perspective remembering associated with egocentric processing. Moreover, whereas the hippocampus may integrate elements of an episodic memory such as space and time (Burgess et al, 2002;Eichenbaum, 2014), AnG may integrate sensory elements of multimodal memories into a complete and vivid recollection. Examining the possible functional dissociation between these two regions is a critical next step for future research.…”
Section: Angular Gyrus and Episodic Memorymentioning
confidence: 99%
“…Direct evidence from single-neuron recordings in rats indicates that cells in the hippocampus fire in specific spatial locations (2)(3)(4)(5)(6) or at specific times during a temporal delay (7,8). Single-neuron and functional MRI (fMRI) studies in individuals navigating virtual environments have confirmed that cells coding for spatial location are also present in the human hippocampus (9)(10)(11).…”
mentioning
confidence: 99%
“…Converging evidence from human and animal studies point to entorhinal cortical (EC)-hippocampal (HPC) circuits as being critical for episodic memory, and in particular for temporal associative learning (Eichenbaum 2014, MacDonald 2014. In this regard, Pavlovian conditioning protocols (Maren 2001) have proven especially useful.…”
mentioning
confidence: 99%
“…These two protocols, along with additional control conditions (e.g., unpaired pseudo-random CS-US presentations), provide a powerful means to evaluate the contribution of different brain regions to temporal associative learning. For these reasons, in this review we focus discussion primarily on these behavioral paradigms, the functional dissections of the EC-HPC circuits and the physiological mechanisms that subserve temporal aspects of episodic memory, although there are reviews that discuss additional physiological mechanisms of temporal associative learning (Hasselmo and Stern 2006;Yoshida et al 2012;Eichenbaum 2014).…”
mentioning
confidence: 99%